Does College Matter? Exploring College-Level Factors Related to Victimization Risk for U.S. and Canadian College Students - Daigle, Leah E. (International journal of offender therapy and comparative criminology, 2024)
Research shows that U.S. college students are at risk for a variety of victimization types. College students in Canada also experience similar types of victimization compared to U.S students, yet recent research shows that Canadian students are at a greater risk than U.S. college students of being victimized. Little is known, however, as to whether college-level factors influence victimization risk and how these risks may be different for U.S. and Canadian college students. Using the American College Health Association’s National College Health Assessment data (ACHA-NCHA II), the current study builds upon past research by exploring the role of both individual and school characteristics and whether they are similarly related to risk of victimization in the two populations. The findings show that Canadian students are at higher risk for victimization and that some school-level factors play a role in predicting this risk for all students, with some variation in ones that matter for each country.